2005
DOI: 10.1002/pmic.200401024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of secretory proteins from pathogenic and nonpathogenicListeriaspecies

Abstract: Extracellular proteins of bacterial pathogens play a crucial role in the infection of the host. Here we present the first comprehensive validation of the secretory subproteome of the Gram positive pathogen Listeria monocytogenes using predictive bioinformatic and experimental proteomic approaches. The previous original signal peptide (SP) prediction (Glaser et al., Science 2001, 294, 849-852) has been greatly improved by an in-depth analysis using seven different bioinformatic tools. Subsequent careful classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 62 publications
6
160
0
Order By: Relevance
“…The autolysins P60 and MurA, which contain two and four LysM domains, respectively, are present in purified cell wall fractions (34). Lmo1303 and Lmo2522, which contain one and two LysM domains, respectively, are detected in supernatant fractions, indicating that these proteins can translocate across the plasma membrane (179). One LysM domain is also found in Lmo1941, a protein with a transmembrane hydrophobic domain that is detected in the L. monocytogenes membrane fraction (193).…”
Section: Proteins With Noncovalent Association To the Cell Wallmentioning
confidence: 88%
See 2 more Smart Citations
“…The autolysins P60 and MurA, which contain two and four LysM domains, respectively, are present in purified cell wall fractions (34). Lmo1303 and Lmo2522, which contain one and two LysM domains, respectively, are detected in supernatant fractions, indicating that these proteins can translocate across the plasma membrane (179). One LysM domain is also found in Lmo1941, a protein with a transmembrane hydrophobic domain that is detected in the L. monocytogenes membrane fraction (193).…”
Section: Proteins With Noncovalent Association To the Cell Wallmentioning
confidence: 88%
“…Proteomic studies identified proteins that have no predicted signal sequence, and are assumed to have cytoplasmic functions, in the L. monocytogenes cell wall or supernatant fractions (160,179). Among them are glycolytic enzymes, chaperones, and heat shock proteins, as well as proteins involved in detoxification and adaptation to atypical conditions, nucleic acid metabolism, transcription, and translation.…”
Section: Nonconventional Secreted Surface Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic approach has been successfully used to address a global view of bacterially physiological issues (15)(16)(17)(18)(19)(20). Here, we compared S. pyogenes secretome samples from the wild-type strain and the perR deficient mutant by using gel-based proteomics analysis for discovery of novel PerR-regulated extracellular virulence factors.…”
mentioning
confidence: 99%
“…Secretome analysis of various pathogenic bacteria, including Aeromonas hydrophila, L. monocytogenes, H. pylori, B. anthracis, B. subtilis, S. aureus and Pseudomonas aeruginosa, has not only identified known virulence factors, but has also revealed previously uncharacterized secreted proteins that were involved in pathogenesis Nouwens et al, 2002;Tjalsma et al, 2004;Trost et al, 2005;Chitlaru et al, 2006;Sibbald et al, 2006;Yu et al, 2007). For example, in S. aureus, the function of the diacylglycerol transferase (Lgt) virulence factor was revealed by comparing the exoproteomes of wild type and Lgt mutants with impaired virulence (Sibbald et al, 2006).…”
Section: Secretome/exoproteomementioning
confidence: 99%